Anti-salivary gland protein 1 antibodies in two patients with Sjogren’s syndrome: two case reports - Vishwanath, Sahana (BioMed Central, 2014)
INTRODUCTION: Current diagnostic criteria for Sjogren’s syndrome developed by the American College of Rheumatology include the presence of antinuclear antibodies, rheumatoid factor, anti-Ro or anti-La autoantibodies. The purpose of this report is to describe two patients with biopsy-proven Sjogren’s syndrome lacking these autoantibodies but identified by antibodies to salivary gland protein 1. Diagnosis was delayed until salivary gland tumors developed in these patients because of the lack of the classic autoantibodies. This report emphasizes the existence of patients with primary Sjogren’s syndrome who lack autoantibodies anti-Ro or anti-La and may therefore be misdiagnosed. Antibodies to salivary gland protein 1 identify some of these patients. CASE PRESENTATION: Two patients are described and were seen in the autoimmune disease clinics of the State University of New York (SUNY) at the Buffalo School of Medicine. In both patients, chronic dry mouth and dry eye had been dismissed as idiopathic because test results for autoantibodies anti-Ro and anti-La were negative. Both patients had swelling of major salivary glands that prompted biopsies. Biopsies of major salivary glands from both cases demonstrated salivary gland tumors and existence of inflammation consistent with Sjogren’s syndrome. Serologic testing revealed antibodies to salivary gland protein 1. CONCLUSIONS: Patients presenting with classic clinical symptoms of dry mouth and eyes do not always show the current serologic markers of Sjogren’s syndrome, anti-Ro and anti-La. In these cases, investigation for antibodies to salivary gland protein 1 is of importance to make the diagnosis of Sjogren’s syndrome. Early diagnosis of Sjogren’s syndrome is necessary for improved management as well as for vigilance regarding potential complications, such as salivary gland tumors as were seen in the described cases.